2016
DOI: 10.1136/bmjopen-2016-011582
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of one-to-one volunteer support for patients with psychosis: protocol of a randomised controlled trial

Abstract: IntroductionSocial isolation is common in patients with psychosis and associated with a number of negative outcomes. Programmes in which volunteers provide one-to-one support—often referred to as befriending—have been reputed to achieve favourable outcomes. However, trial-based evidence for their effectiveness is limited.Methods and analysisThis is a randomised controlled trial comparing the effects of one-to-one volunteer support with an active control condition for patients with psychosis over a 1-year perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…We conducted a parallel groups RCT in community-based mental health services in London, UK, between August 2015 and August 2017 (full details in the published protocol) 18 . Patient-participants were recruited from 15 community services across the London boroughs of City and Hackney, Tower Hamlets and Newham.…”
Section: Methodsmentioning
confidence: 99%
“…We conducted a parallel groups RCT in community-based mental health services in London, UK, between August 2015 and August 2017 (full details in the published protocol) 18 . Patient-participants were recruited from 15 community services across the London boroughs of City and Hackney, Tower Hamlets and Newham.…”
Section: Methodsmentioning
confidence: 99%
“…The question and answer categories were based on a wider research programme on befriending for patients with mental illness conducted at the Unit for Social and Community Psychiatry at Queen Mary University of London [6, 18, 22]. They reflected themes identified in a systematic review of volunteering in mental health settings [18] and were further refined in a consultative process involving experts working in volunteering organisations in Austria.…”
Section: Methodsmentioning
confidence: 99%
“…159,160 Similarly, another large study, 159 also using the EQ-5D-3L, looked at the use of antipsychotics in a population with schizophrenia and found that the baseline mean utility was 0.61 to 0.67 (SD 0.29 to 0.33; n = 118). Finally, a recent large study 176 (n = 275) of schizophrenia reported higher values using the EQ-5D-5L, with reported baseline utility values between 0.74 and 0.76.…”
Section: Discussionmentioning
confidence: 88%